Hukum Jual Beli Online dengan Sistem Pre Order dalam Perspektif Hukum Islam (Studi Kasus Toko Online Nashrah Store) - Hendra Wijaya; Askar Patahuddin; Aqbar, Khaerul; Wahyu Kurniawan Hasmudin (BUSTANUL FUQAHA: Jurnal Bidang Hukum Islam, 2021)
This study aimed to know and anlayze the process of buying and selling online with a pre-order system at the Nashrah Store online store according to Islamic law. This study was a qualitative type of research (field research) using a normative and sociological juridical approach. The research showed several things. First, in general, the process of buying and selling with a pre-order system carried out by Nashrah Store is in accordance with the laws governing electronic transaction. Second, the sale and purchase contract carried out by Nashrah Store based on the form and method of payment are to apply a salam contract. As for the final payment method, it does not apply a salam contract, but applies al-wa'd bi al-syira' which is only in the form of a purchase promise.